The role of stem cells in uterine involution. Issue 3 (March 2021) - Spooner, Madelyn K; Lenis, Yasser Y; Watson, Rachel; Jaimes, Daniela; Patterson, Amanda L
Abstract : Uterine remodeling during pregnancy and repair postpartum are fundamental to the successful propagation of eutherian species. The most drastic remodeling occurs in species with invasively implanting embryos, including humans and mice. During embryo implantation, embryonic trophoblasts breach the epithelium, penetrating into the stroma. Stromal cell decidualization, which is critical for the establishment and maintenance of early pregnancy, occurs throughout the implantation site. Trophoblasts further invade into and remodel uterine spiral arteries, which is necessary for placental formation. The uterus increases in size up to 24-fold, which is largely attributed to myometrial expansion. Uterine changes that occur during pregnancy must then be resolved postpartum. Following parturition, the uterus repairs the remodeled tissue in the process of uterine involution. During involution, the majority of the endometrium is regenerated to replace the tissue that is shed postpartum. The myometrium returns to the pre-gravid state which is thought to occur through apoptosis and autophagy of smooth muscle cells. Although we understand the general process of postpartum uterine involution, the detailed mechanisms, particularly the role of putative stem cells, are poorly understood. This review discusses the evidence for the existence of epithelial, stromal and myometrial stem cells and their role in uterine involution. Gaps in knowledge and areas for future research are also considered. Studies of both postpartum and menstrual uterine repair, which likely involve similar mechanisms, are described under the broad definition of uterine involution. Although the primary focus of this review is human, mouse models are discussed to provide additional information.